An analysis of the representation of organizational practices in a TV drama of Korea: Implications of public pedagogy for critical human resource development - Hanbyul Kim (Adult Education Research Conference, 2023)
This study aims to analyze a Korean TV drama for the purpose of addressing the ideological influences of popular culture on workers' practice in organizations.
Keywords: critical HRD; Public pedagogy; Popular culture; Informal learning